Cyclooxygenase-2 Gene 765 single nucleotide polymorphism as a protective factor against periodontitis in Taiwanese - Ya-Ping Ho, Ying-Chu Lin (Blackwell Synergy, 2008)
Aim: Prostaglandin E2 (PGE2) is considered to be an important mediator of tissue destruction in periodontitis. The cyclooxygenase (COX) catalyses the production of PGs. COX-2, which is induced in an inflammatory response, is responsible for PGs synthesis at sites of inflammation. A single nucleotide polymorphism of COX-2 765 has been shown to alter the expression of the COX-2 gene. The purpose of the present study was to evaluate the association of the COX-2 765 polymorphism and susceptibility to periodontitis in Taiwanese.